2021
DOI: 10.1371/journal.pone.0251642
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of diabetic peripheral neuropathy in Latin America and the Caribbean: A systematic review and meta-analysis

Abstract: Aims The objective of this systematic review and meta-analysis is to estimate the prevalence and incidence of diabetic peripheral neuropathy (DPN) in Latin America and the Caribbean (LAC). Materials and methods We searched MEDLINE, SCOPUS, Web of Science, EMBASE and LILACS databases of published observational studies in LAC up to December 2020. Meta-analyses of proportions were performed using random-effects models using Stata Program 15.1. Heterogeneity was evaluated through sensitivity, subgroup, and meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 85 publications
(207 reference statements)
1
30
1
2
Order By: Relevance
“…There was no statistically significant association between gender and DPN (p = 0.966). Previous studies showed that the prevalence of DPN was different among adults with diabetes depending on the nation, age, duration of diabetes, glucose control, and type 1 versus type 2 diabetes from 9.6% to 69% in Latin and American countries 1 , 26 , 27 from 30.1% to 58% in Asian countries. 28 , 29 Thus, the prevalence of DPN in our study was lower than that in other Asian countries due to several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no statistically significant association between gender and DPN (p = 0.966). Previous studies showed that the prevalence of DPN was different among adults with diabetes depending on the nation, age, duration of diabetes, glucose control, and type 1 versus type 2 diabetes from 9.6% to 69% in Latin and American countries 1 , 26 , 27 from 30.1% to 58% in Asian countries. 28 , 29 Thus, the prevalence of DPN in our study was lower than that in other Asian countries due to several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic peripheral neuropathy (DPN) is the most common complication of diabetes in general and occurs early. 1–3 Diabetic neuropathy is a type of nerve damage all over the body and can alter autonomic motor, and sensory functions. 4 DPN is the most common form of diabetic neuropathy, affecting the outer nerves of the limbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we downgraded the evidence one level j Imprecision was not present, due to a narrow CI and adequate sample size. So we did not downgrade the level of certainty * This study was downgraded below the level of very low (2 levels) † This study was downgraded below the level of very low (1 level) Refs [ 2 , 4 , 65 , 76 , 99 ]…”
Section: Resultsmentioning
confidence: 99%
“…The certain of evidence assessment was conducted as in our previously published articles [ 2 , 65 , 99 ]. We adapted the evaluation for prevalence meta-analysis using the five domains described in the GRADE handbook as follows: study limitations (the risk of bias of the primary studies), imprecision (appropriateness of the sample size and width of the CI), indirectness (generalizability of results), inconsistency (between-study heterogeneity), and publication bias [ 76 ].…”
Section: Methodsmentioning
confidence: 99%